(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
In this article, the development of analytical observation skills in students is studied as a socio-pedagogical necessity. Also, consistent and thorough opinions were given that in the current period, young people are given enough opportunities to apply their professional knowledge in life, and that the provision of this task can raise the quality of education to a high level